2013
DOI: 10.1021/es400032v
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a Novel Flame Retardant Known as V6: Measurements in Baby Products, House Dust, and Car Dust

Abstract: With the phase-out of polybrominated diphenyl ether (PBDE) flame retardants, the use of new and alternate flame retardants has been increasing. 2,2-bis(chloromethyl)propane-1,3-diyltetrakis(2-chloroethyl) bisphosphate, known as V6, is a flame retardant applied to polyurethane foam commonly found in furniture and automobile foam. However, to the authors’ knowledge, no research has been conducted on V6 levels in the environment. The intention of this study was to measure the concentration of V6 in foam collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 22 publications
1
52
2
Order By: Relevance
“…It has been suggested that if ESI(+) is used for quantification of OPEs, the standard addition procedure should be used [21]. APCI seems more suitable than ESI for this purpose because in APCI the main ionization process happens in gas phase, which largely reduces ion-suppression [12,22,31]. In the present method, with optimized APCI(+) operation parameters the ME values for the analytes in pork liver or chicken egg samples ranged from 40 to 94% (Table 3) and much improved compared to using the ESI source.…”
Section: Determination By Uhplc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that if ESI(+) is used for quantification of OPEs, the standard addition procedure should be used [21]. APCI seems more suitable than ESI for this purpose because in APCI the main ionization process happens in gas phase, which largely reduces ion-suppression [12,22,31]. In the present method, with optimized APCI(+) operation parameters the ME values for the analytes in pork liver or chicken egg samples ranged from 40 to 94% (Table 3) and much improved compared to using the ESI source.…”
Section: Determination By Uhplc-msmentioning
confidence: 99%
“…In addition to high concentration levels found in house dust samples, they have also been determined in municipal wastewater, surface and drinking water as well as human breast milk, fish and some other biota samples [3][4][5]9,[11][12][13][14][15][16][17]. OPEs elicit genotoxic and neurotoxic effects [18] and some chlorinated OPEs have log Kow values ranging from 1 to 5 indicating the potential to persist and bioaccumulate in the environment [1,3,19].…”
Section: Introductionmentioning
confidence: 99%
“…nursing pillows). They are commonly added to flame retardant mixtures, such as Firemaster ® 550 (FM550), and to other consumer products as plasticizers (Ballesteros-Gomez et al 2014; Fang et al 2013; Patisaul et al 2013; Stapleton et al 2008; Stapleton et al 2009; Stapleton et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…One complex matrix type of significant research interest for the study of flame retardants is dust . Dust is a sink for semi‐volatile compounds, including flame retardants and is easily collected from outdoors and indoor microenvironments of homes , offices , hotels , cars , day‐care centers and schools where it can be selectively sampled from furniture or electronics . Other research groups have sampled dust at production or recycling facilities given the high volume of consumer electronics being produced or recycled annually.…”
Section: Introductionmentioning
confidence: 99%